The Effectiveness of Counter-Narratives in Information Warfare: A Systematic Review for National Security Resilience - Jay Aryaputra Singgih; Robby Mochamad Taufik; Guntur Eko Saputro (Goodwood Publishing, 2026)
Purpose: This study aims to systematically identify and evaluate the effectiveness of various counter-narrative strategies in responding to the threats of disinformation and hybrid warfare, given that information warfare has evolved into a cognitive threat targeting public psychology and the pillars of democracy. Research Methodology: Using the Systematic Literature Review (SLR) method, this study analyzed 20 core articles selected from the Dimensions database (screened from 8,425 initial results) with a publication range of 2023–2025. Data were synthesized using thematic analysis. Results: The findings indicate that the effectiveness of counter-narratives is not determined by their intrinsic factual truth but rather depends heavily on the alignment of the narrative with the worldview and media consumption habits of the target audience. Conclusions: This study concludes that effective counter-narrative strategies have shifted from reactive responses (debunking) to proactive interventions (pre-bunking) and strategic leadership narratives (statecraft) over the years. Successful implementation requires a coordinated, AI-enabled response architecture, which presents a fundamental dilemma for democracies regarding the balance between national security and freedom of speech. Limitations: This study was limited to academic literature indexed in the Dimensions database, potentially excluding relevant grey literature or closed policy documents. Contributions: This study provides strategic insights into the evolution of information warfare responses, highlighting the necessity of proactive measures and ethical challenges in protecting democratic values against cognitive threats.